The Application of Motion Pattern Recognition in the Behaviometrics of Human Kinematics - Andar Bagus Sriwarno (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2009)
Current trends seem to accredit motion as a sensible biometric feature for human identification in spite ofphysiological parameter which related to the shape of the body. As in many image processing system, therecognition is running under the circumstances of the lighting condition that may moving object acquitioned bythe computer. Through this principes, this paper presents the application of video inter-frame analysis systemfor determining human motion from the sagittal view video sequences. By using this method, the behavior ofperson can be recognized and determined the type of motion. Some researches have coined the termbehaviometrics for this class of biometrics. The experiment was conducted by asking subjects to conduct thesimple motion. Eight healthy male subjects participated in the experiment to raise from the deep squatting (STS)at the three different foot elevations: full squatting (FS) which the plantar feet were fully contact to the floor (0degree), slope squatting (SS) which a 15 degrees of wedge was applied underneath the feet, and tiptoe squatting(TS) which subjects rose the heel by extending the metatarsal joint at their preferred height. The result showedthat raising the heel significantly affected the postural adjustment that at TS condition was significantly smallerin forward displacement on the knee and the hip during ankle dorsiflexion and influenced to short the time takenat the forward movement to conduct STS movement than shown at FS and SS. Significant differences were alsoappeared in the parameter of task period and segmental body angle. These findings suggest that the differencesway to achieve STS movement in some ways can contribute to decrease task period and to differ the pattern ofmotion that furthermore supports the identification in behaviometrics.Keywords: behaviometrics, motion pattern, video acquitition.